Youth Health Literacy: Lessons from the Field. Issue 1 (2nd January 2018) - Parker, Catherine M.; Coghill, Jeffrey G.
ABSTRACT: The Youth Health Literacy Project targeted middle and high school students in a rural county who were enrolled in health and physical fitness classes. Students were instructed on good, reliable health information websites using the Internet. The authors also loaned each student an Amazon Kindle Fire tablet to gauge the student's grasp of health literacy information. A pretest and posttest measured the effectiveness of the instruction.